Intestinal Flagellated Giardia Lamblia: A Systematic Review: Intestinal Flagellated Giardia Lamblia: A Systematic Review - Arabyaghoubi, Mostafa (International Journal of Pharmaceutical & Biological Archive, 2018)
There are four main common types of flagellated phlebotomy parasites: Giardia lamblia, Chilomastix Mesnili, Trichomonas hominis, and De Anenoba fragilis. In addition, there are also two other little tickles called Entropia hominis and retortamonas intestinalis. Except for Giardia and DeAneoba, there is no evidence of pathogenicity of other intestinal flagellated parasites. A pathogenic trichomoniasis called Trichomonas vaginalis is located in the genitourinary tract and another flagellated, called Trichomonas tenax, is found in the mouth. Searches were conducted by two independent researchers in international (PubMed, Web of Science, Scopus, and Google Scholar) and national (SID and Magiran) databases for related studies from the inception of the databases to September 2017 (without time limitation) in English and Persian languages. To ensure literature saturation, the reference lists of included studies or relevant reviews identified through the search were scanned. The detection of the parasite is done to find the trophozoites in the fluids in the duodenum by intubating or inserting the yarn into the duodenum (enterostate) or duodenal biopsy. In addition, giardiasis can be used to determine the presence of parasites in fecal samples by ELISA or immunofluorescence, or by searching for antigens of Giardia in the stool by counterimmunoelectrophoresis, ELISA, and enzyme immunoassay